Lower limb MSK injuries among school-aged rugby and football players: a systematic review. Issue 1 (28th October 2020) - Anderson, David Stewart; Cathcart, John; Wilson, Iseult; Hides, Julie; Leung, Felix; Kerr, Daniel
Abstract : Objective: The objective of this systematic review was to explore the incidence of lower limb musculoskeletal (MSK) injuries sustained by rugby union, rugby league, soccer, Australian Rules and Gaelic football players under 18 years. The review sought to identify the mechanisms and types of injury sustained and to compare between sports. Design: This systematic review focused on the incidence of lower limb injury in adolescent team sports that involved running and kicking a ball. A literature search of studies published prior to January 2020 was conducted using SportDiscus, Medline and PubMed databases. The Standard Quality Assessment Criteria appraisal tool was used to assess the quality of each article included in the review. Two or more authors independently reviewed all papers. Results: Sixteen papers met the inclusion criteria; prospective cohort (N=14), retrospective (n=1) and longitudinal (n=1). These studies investigated injuries in rugby union and rugby league (n=10), football (soccer) (n=3), Australian Rules (n=2) and Gaelic football (n=1). There were a total of 55 882 participants, aged 7–19 years old, who reported 6525 injuries. The type, site and mechanisms of injury differed across sports. Summary: Lower limb injuries were common in adolescent rugby, soccer, Gaelic football and Australian Rules football players, however these studies may not fully reflect the true injury burden where recurrent and overuse injuries have not been considered. There were differences between sports in the mechanisms, types and severity of injury.